2004
DOI: 10.1523/jneurosci.2251-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Synaptic Function in the Microglial KARAP/DAP12-Deficient Mouse

Abstract: Several proteins are expressed in both immune and nervous systems. However, their putative nonimmune functions in the brain remain poorly understood. KARAP/DAP12 is a transmembrane polypeptide associated with cell-surface receptors in hematopoeitic cells. Its mutation in humans induces Nasu-Hakola disease, characterized by presenile dementia and demyelinization. However, alteration of white matter occurs months after the onset of neuropsychiatric symptoms, suggesting that other neuronal alterations occur in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
172
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(176 citation statements)
references
References 57 publications
2
172
0
2
Order By: Relevance
“…Furthermore, we reported that in the healthy adult murine CNS, only subsets of microglia expressed Trem2 mRNA as assayed by in situ hybridization analysis [15]. However, in vitro studies indicated the potential for oligodendrocytes to express Trem2 and DAP12 while DAP12KO mice were observed to display modest myelin abnormalities [19][20][21][22]. Here we directly characterize microglial and oligodendrocyte expression of Trem2 and DAP12 by dual immunohistochemistry/in situ hybridization analysis during post-natal period of oligodendrocyte development and myelination.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Furthermore, we reported that in the healthy adult murine CNS, only subsets of microglia expressed Trem2 mRNA as assayed by in situ hybridization analysis [15]. However, in vitro studies indicated the potential for oligodendrocytes to express Trem2 and DAP12 while DAP12KO mice were observed to display modest myelin abnormalities [19][20][21][22]. Here we directly characterize microglial and oligodendrocyte expression of Trem2 and DAP12 by dual immunohistochemistry/in situ hybridization analysis during post-natal period of oligodendrocyte development and myelination.…”
Section: Discussionmentioning
confidence: 89%
“…First, histological analysis of adult CNS tissue from DAP12 knock-out mice in studies by two separate groups revealed modest, diffuse hypomyelination in anterior brain regions that was associated with substantial reductions in CNS microglia [20][21][22]. Subsequent gene profiling studies of CNS mRNA isolated from DAP12KO mice by a third group revealed decreased expression of selected myelin transcripts [23].…”
Section: Introductionmentioning
confidence: 99%
“…This discrepancy could relate to different experimental culture conditions. Finally, impaired synaptic function has been reported in the brain of KARAP/DAP12-deficient mice, correlating KARAP/DAP12 deficiency with both histological and functional brain alterations [53].…”
Section: Karap/dap12 In the Brainmentioning
confidence: 91%
“…The KARAP/DAP12-dependent mechanisms responsible for this brain pathology are still unknown. KARAP/DAP12 expression is detectable in human and mouse brain, in particular in microglial cells [46,51,53]. Controversial data have been published regarding KARAP/DAP12 expression in in-vitro-cultured oligodendrocytes, cells primarily involved in the production of myelin sheath [50,51,53].…”
Section: Karap/dap12 In the Brainmentioning
confidence: 99%
“…Tumor-associated microglia constitute the main population of brain immune cells (Graeber et al, 2002) and are important for monitoring their local environment, regulating function and apoptosis, and secreting proinflammatory cytokines (Banati et al, 1993;Elkabes et al, 1996;Marı´n-Teva et al, 2004;Roumier et al, 2004). These resident brain immune system mononuclear cells can be recruited by glioma tumors cells to the local tumor microenvironment by vascular Figure 3 Co-evolution of neoplastic and non-neoplastic cells in gliomas.…”
Section: Stromal Determinants Of Glioma Formation and Growthmentioning
confidence: 99%